2021
DOI: 10.1088/1361-6528/abdb16
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive model toward optimization of SAG In-rich InGaN nanorods by hydride vapor phase epitaxy

Abstract: Controlled growth of In-rich InGaN nanowires/nanorods (NRs) has long been considered as a very challenging task. Here, we present the first attempt to fabricate InGaN NRs by selective area growth using hydride vapor phase epitaxy. It is shown that InGaN NRs with different indium contents up to 90% can be grown by varying the In/Ga flow ratio. Furthermore, nanowires are observed on the surface of the grown NRs with a density that is proportional to the Ga content. The impact of varying the NH3 partial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…In our previous work, we have shown that the optimal deposition temperature for SAG of GaN by HVPE is 980 °C [23,25]. A temperature range of 880 °C-980 °C was used in this study.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In our previous work, we have shown that the optimal deposition temperature for SAG of GaN by HVPE is 980 °C [23,25]. A temperature range of 880 °C-980 °C was used in this study.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Прежде всего это связано со сложностью получения низкодефектных пленок InGaN. Для решения данной проблемы авторы ряда работ [1][2][3] предлагают при создании гетероструктур вместо эпитаксиальных сплошных слоев, содержащих индий, использовать нитевидные нанокристаллы (ННК), поскольку в самих нанокристаллах практически не образуются дислокации несоответствия [4]. Отметим, что основная часть работ посвящена росту методами молекулярно-пучковой эпитаксии или газофазной эпитаксии из металлоорганических соединений.…”
Section: поступило в редакцию 20 октября 2021 г в окончательной редакции 20 октября 2021 г принято к публикации 15 ноября 2021 гunclassified